Penerapan Arsitektur Tropis pada Dionumo Cottage - Berni Hantu; Heryati Heryati; Abdi Gunawan Djafar (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2026)
Tourism is a potential sector in supporting regional development, with adequate facilities and infrastructure as essential factors to ensure visitor comfort. Dionumo Island in Gorontalo possesses attractive natural resources; however, its tourism facilities, particularly accommodations, remain limited. This study aims to design Dionumo Cottage as a tourist accommodation facility using a tropical architecture approach, emphasizing climate adaptation, harmony with nature, and the use of appropriate forms, functions, and materials. The research employs a qualitative method through observation, interviews, and literature studies from various sources. The collected data were analyzed to identify tourist needs, site conditions, and applicable principles of tropical architecture. The design results indicate that applying tropical architecture to Dionumo Cottage can provide environmentally integrated accommodation facilities, enhance tourist comfort, and contribute to sustainable tourism development in Gorontalo.